R.A. Fisher, eugenics, and the campaign for family allowances in interwar Britain - Aylward, A (Cambridge University Press, 2021)
Ronald Aylmer Fisher (1890–1962) is today remembered as a giant of twentieth-century statistics, genetics and evolutionary theory. Alongside his influential scientific contributions, he was also, throughout the interwar years, a prominent figure within Britain's eugenics movement. This essay provides a close examination of his eugenical ideas and activities, focusing particularly upon his energetic advocacy of family allowances, which he hoped would boost eugenic births within the more ‘desirable’ middle and upper classes. Fisher's proposals, which were grounded in his distinctive explanation for the decay of civilizations throughout human history, enjoyed support from some influential figures in Britain's Eugenics Society and beyond. The ultimate failure of his campaign, though, highlights tensions both between the eugenics and family allowances movements, and within the eugenics movement itself. I show how these social and political movements represented a crucial but heretofore overlooked context for the reception of Fisher's evolutionary masterwork of 1930, The Genetical Theory of Natural Selection, with its notorious closing chapters on the causes and cures of national and racial decline.